2007
DOI: 10.1002/job.512
|View full text |Cite
|
Sign up to set email alerts
|

How does coaching interviewees affect the validity of a structured interview?

Abstract: SummaryCoaching interviewees to perform in employment interviews can influence the interview scores. We describe different types of coaching, emphasizing interventions designed to focus interviewees on core, interview-relevant content and to help them convey the content accurately (as opposed to interventions designed to teach interviewees to manipulate their scores using peripheral means). We then study the effects of the former type of intervention in relation to the criterion-related validity of a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The first level involves making sure that applicants do not get any information about the assessed dimensions (König, Melchers, Kleinmann, Richter, & Klehe, 2007). The second level is making applicants aware of the dimensions on which they would be rated in interviews (Allen, Facteau, & Facteau, 2004;Klehe, König, Richter, Kleinmann, & Melchers, 2008;Maurer, Solamon, & Lippstreu, 2008;McFarland, Ryan, Sacco, & Kriska, 2004). The third level is giving applicants a list of questions before the interview (Day & Carroll, 2003;Personnel Decisions International, 1997).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The first level involves making sure that applicants do not get any information about the assessed dimensions (König, Melchers, Kleinmann, Richter, & Klehe, 2007). The second level is making applicants aware of the dimensions on which they would be rated in interviews (Allen, Facteau, & Facteau, 2004;Klehe, König, Richter, Kleinmann, & Melchers, 2008;Maurer, Solamon, & Lippstreu, 2008;McFarland, Ryan, Sacco, & Kriska, 2004). The third level is giving applicants a list of questions before the interview (Day & Carroll, 2003;Personnel Decisions International, 1997).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Four studies (Allen et al., ; Day & Carroll, ; Klehe et al., ; Maurer et al., ) compared transparent and nontransparent interviews and found that transparency led to higher interview ratings. Transparency was also shown to increase (a) construct validity (Klehe et al., ); (b) reliability and predictive validity (Maurer et al., ); (c) applicants’ perception of fairness; and (d) it did not decrease criterion‐related validity of interviews (Day & Carroll, ). Yet, König et al.…”
Section: Definition Of Structurementioning
confidence: 99%
“…Thus, it remains unclear as to whether interview training can reduce participants’ interview anxiety. For our study we assume that VI training should reduce participants’ interview anxiety in contrast to a control training group because it allows participants to individually experience and actively perform, which is more realistic of a job interview (Maurer, Solamon, & Lippstreu, ). Thus, we propose the following additional meditation mechanism:
Hypothesis 2c : The effect of VI training on participants’ interview performance will be mediated by lower interview anxiety. Hypothesis 2d : The effect of VI training on participants’ hireability ratings will be mediated by lower interview anxiety.
…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, it remains unclear as to whether interview training can reduce participants' interview anxiety. For our study we assume that VI training should reduce participants' interview anxiety in contrast to a control training group because it allows participants to individually experience and actively perform, which is more realistic of a job interview (Maurer, Solamon, & Lippstreu, 2008). Thus, we propose the following additional meditation mechanism:…”
Section: Hypothesis 2bmentioning
confidence: 99%
“…A better understanding of the properties of applicants' responses to behavioral questions could lead to several improvements in interview practice. For example, it may be possible to teach applicants to produce meaningful and representative stories as part of training programs (Maurer et al 2008;Ralston et al 2003). And interviewers may be better trained to help applicants produce such stories (e.g., by appropriate prompting).…”
Section: Introductionmentioning
confidence: 99%